On non-archimedean Frechet spaces with nuclear Kothe spaces - Śliwa, Wiesław (The American Mathematical Society, 2010)
Assume that K is a complete non-archimedean valued field. We prove that every Frechet-Montel space over K which is not of finite type has a nuclear Kothe quotient.
Keywords: Kothe quotient; Orthogonal basis